Autoantibodies to N-methyl D-aspartate receptors in autoimmune encephalitis - Bera, K (2011)
N-methyl-D-aspartate receptor (NMDAR) antibody encephalitis is a recently described autoimmune encephalopathy defined by the presence of serum antibodies that bind NMDARs (NMDAR-Abs). NMDAR-Ab encephalitis is a severe, but treatmentresponsive encephalitis with subacute onset. It can be associated with tumours and affects mainly young adults. Patients present with cognitive dysfunction, seizures, psychiatric and sleep disorders and most develop dyskinesias, autonomic instability and reduced consciousness. To explore further the NMDAR-Abs and their potential pathogenicity, a series of in vitro investigations were performed and preliminary attempts at passive transfer of disease. Human embryonic kidney (HEK) cells transfected with the NR1 and NR2B subunits, and live cultured neurons, were used first to detect NMDAR-Ab binding. Immunocytochemistry and ow cytometry demonstrated that binding to transfected HEK cells could be improved when NMDAR were presented in clusters by cotransfection with the postsynaptic density protein PSD-95. The NR1 subunit was identified as the target of NMDAR-Abs, and a novel quantitative assay based on immunoprecipitation of NR1 tagged by fusion with green uorescent protein was developed. Measurement of NMDAR-Ab levels showed that antibody levels corresponded to the clinical disease score within individual patients. Although the purification of full length NR1 was not successful, a secreted N-terminal construct was created and expressed in HEK cells. The binding of NMDAR-Abs was confirmed and this construct will be used for active immunisation in future. To explore pathogenic mechanisms in vitro, the main antibody subclasses were shown to be IgG1 and IgG3. Moreover the patients' autoantibodies, but not healthy control antibodies, were able to activate the complement cascade in vitro in cell lines and primary cultures. Finally, the NMDAR-Abs were shown to bind to primary microglial cultures and to cause morphological changes corresponding to early activation processes after prolonged exposure. The research has developed new assays that could be used for diagnosis and serial studies and revealed new potential mechanisms in NMDAR-Ab encephalitis.